2009
DOI: 10.1111/j.1464-410x.2008.08324.x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of sildenafil citrate on bladder outlet obstruction: a mouse model

Abstract: BOO mediates both functional and structural changes in the mouse bladder. Six weeks of obstruction caused an increase in BC, detrusor overactivity and voiding pressure, and mediated an increase in bladder weight, detrusor muscle hypertrophy and collagen deposition in the lamina propria and smooth muscle. Treatment with 6 weeks of oral sildenafil beginning at the time of BOO prevented the increase in detrusor overactivity without affecting voiding pressures, and prevented the increase in detrusor muscle hypertr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
37
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(42 citation statements)
references
References 21 publications
4
37
1
Order By: Relevance
“…In addition, it has been observed that a chronic 4-week treatment with vardenafil significantly reduced the number of nonvoiding contractions in BOO rats, and may suggest a way to reduce irritative symptoms ( [34] further extended these results by showing that a 4-week treatment of BOO rats with vardenafil restored the contractile response in the bladder, implying that vardenafil had bladder protective effects. Finally, these data were confirmed by findings in mice, in which a 6-week oral treatment with sildenafil showed bladder protective effects [35]. Interestingly, in this study, sildenafil also decreased bladder muscular hypertrophy and bladder collagen levels, resulting in an increase in bladder capacity compared with placebo that had not been reported in other studies [35].…”
Section: Effects On the Bladdersupporting
confidence: 89%
See 1 more Smart Citation
“…In addition, it has been observed that a chronic 4-week treatment with vardenafil significantly reduced the number of nonvoiding contractions in BOO rats, and may suggest a way to reduce irritative symptoms ( [34] further extended these results by showing that a 4-week treatment of BOO rats with vardenafil restored the contractile response in the bladder, implying that vardenafil had bladder protective effects. Finally, these data were confirmed by findings in mice, in which a 6-week oral treatment with sildenafil showed bladder protective effects [35]. Interestingly, in this study, sildenafil also decreased bladder muscular hypertrophy and bladder collagen levels, resulting in an increase in bladder capacity compared with placebo that had not been reported in other studies [35].…”
Section: Effects On the Bladdersupporting
confidence: 89%
“…Finally, these data were confirmed by findings in mice, in which a 6-week oral treatment with sildenafil showed bladder protective effects [35]. Interestingly, in this study, sildenafil also decreased bladder muscular hypertrophy and bladder collagen levels, resulting in an increase in bladder capacity compared with placebo that had not been reported in other studies [35]. The results in rats and mice with BOO strongly suggest that vardenafil and sildenafil reduce bladder-derived symptoms in obstructed animals.…”
Section: Effects On the Bladdersupporting
confidence: 88%
“…A 4-week BOO female mice study revealed increased edema and lymphocytic infiltrate in the lamina propria, and hypoxia was seen in the urothelium, lamina propria and detrusor (5). Six-week BOO male investigation showed increase in muscular hypertrophy and fibrosis (22). …”
Section: Discussionmentioning
confidence: 99%
“…PDE5-Is act mainly to relieve the dynamic and static obstruction of the prostate with a direct relaxation of the bladder [8]. Several in vitro studies have reported smooth muscle relaxation in the human bladder neck and prostate in the presence of PDE5-Is [24,25], and relaxation of the bladder neck and decreases in detrusor muscle overactivity have been detected in animal [26] and human studies [27]. Theoretically, the relaxation of the prostate and bladder neck after PDE5-I treatment could increase urinary flow; however, the concomitant relaxation of the detrusor muscle counteracts this effect, thereby preventing the observation of a final improvement in Q max [27].…”
Section: Discussionmentioning
confidence: 99%